PENGEMBANGAN PROBIOTIK BAKTERI ASAM LAKTAT DARI LIMBAH IKAN YANG BERPOTENSI MENURUNKAN KADAR KOLESTEROL DAGING AYAM BROILER STRAIN HUBBART - Astuti, Astuti (Jurnal Penelitian Saintek, 2010)
The aims of this research is to find the influence of giving isolate probiotic BAL Streptococcus thermophillus from the fish waste toward the broilers’ appearance of woof and the degree of broilers’ cholesterol. The research materials are 40 roosters of broiler Strain Lohmann, production of PT Multi Breeder Adirama at the age of 1 week. The probiotic of isolate treatment of Lactate Acid Bacteria (BAL) which is used in this research is Streptococcus thermophillus bacteria in from of freeze dying which comes from Nutrition Biochemical Laboratory, Veterinary Faculty of UGM The treatment I is as the control (without BAL), the number of BAL in treatment II is 106 CFU/ml, the number of BAL in treatment III is 107 CFU/ml, the number of BAL in treatment IV is 108 CFU/ml. The data collection for the degree of cholesterol is done after 28 days. The data which is collected of woof and the degree of broilers’ cholesterol. The research result: the treatment of giving lactate acid bacteria of Streptococcus thermophillus caused the decrease of the degree of broilers’ cholesterol significantly and the best level of BAL is 108 CFU/ml.